Genetic analysis of the complete G gene of viral hemorrhagic septicemia virus (VHSV) genotype Ie isolates from Turkey - Albayrak, H.; Isidan, H.; Kalayci, G.; Ozan, E.; Vakharia, V.N. (2018)
Viral hemorrhagic septicemia virus (VHSV) is an enveloped non-segmented, single-stranded, negative-sense RNA virus that belongs to the Novirhabdovirus genus of the family Rhabdoviridae. This virus causes economically significant diseases in farmed rainbow trout, in Turkey, which is often associated with the transmission of pathogens from European resources. In this study, moribund rainbow trout (Oncorhynchus mykiss) samples were collected during an outbreak of VHSV in a rainbow trout fish farm in Bolu Province of Turkey in 2006. In addition, two VHSV strains were isolated from wild turbot (Scophthalmus maximus) in Trabzon Province of the Black Sea region of Turkey during a field survey. We have sequenced the full-length glycoprotein (G) gene of three VHSV isolates and compared them with 25 previously published gene sequences. Based on a complete gene nucleotide sequence, Turkish VHSV isolates were classified into class Ie of genotype I, which is closely related to GE-1.2 isolate (97.1-97.5% nucleotide identity and 98.2-98.4% amino acid identity) found in Georgia more than 30 years ago. These isolates could be an indigenous type of VHSV distributed in the Black Sea. On the other hand, Turkish isolates have 97.5-97.6% nucleotide identity and 98.8-99% amino acid identity with Finnish, Danish, and Norwegian isolates which are classified under Ib and Id. These results suggest that Turkish VHSV isolates may have orginated from Europe and co-circulated with indigenous strains which can threaten the aquaculture industry in Turkey.